2017
DOI: 10.15578/ifrj.23.1.2017.29-38
|View full text |Cite
|
Sign up to set email alerts
|

STANDARDIZING CPUE OF ALBACORE TUNA (Thunnus alalunga Bonnaterre, 1788) ON TUNA LONGLINE FISHERY IN EASTERN INDIAN OCEAN

Abstract: Albacore (Thunnus alalunga) is the third dominant catch of Indonesian tuna longline fishery operating in the eastern Indian Ocean. The percentage production of albacore catch was reaching up 6% of the total catch of tuna groups in Indonesia. Thi study aims to examine a relative abundance indices using standardized catch per unit of effort (CPUE) of longliner based on albacore tuna. This information will give a valuable input and information to support stock assessment particularly in the regional basis. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
(24 reference statements)
1
0
0
9
Order By: Relevance
“…Year and quarter were the main factors that influenced the CPUE values in this observation compared to season. Seasonal fishing index in the small-scale fisheries also plays an important role to determine CPUE values (Rochman et al, 2017;Wiyono et al, 2006). This is in line with the present study whereby quarter, year, and season showed significant influence on nominal CPUE.…”
Section: Results and Discussion Resultssupporting
confidence: 91%
“…Year and quarter were the main factors that influenced the CPUE values in this observation compared to season. Seasonal fishing index in the small-scale fisheries also plays an important role to determine CPUE values (Rochman et al, 2017;Wiyono et al, 2006). This is in line with the present study whereby quarter, year, and season showed significant influence on nominal CPUE.…”
Section: Results and Discussion Resultssupporting
confidence: 91%
“…Hasil tangkapan per-unit upaya penangkapan (CPUE; Catch per Unit Effort) adalah merupakan jumlah ikan yang didapatkan (jumlah atau berat) yang diperoleh dari sejumlah upaya penangkapan (efforts) pada rentang waktu tertentu. CPUE digunakan sebagai indek kelimpahan suatu spesies ikan dalam suatu perairan yang berarti bahwa adanya perubahan dalam CPUE akan diikuti oleh perubahan stok ikan yang ada dalam suatu perairan [7], [15], [17], [19], [20]. Indeks kelimpahan pada perikanan rawai tuna sebagian besar didasarkan pada indeks CPUE [25].…”
Section: Pendahuluanunclassified
“…Permasalahan utama dalam penghitungan nilai indek CPUE adalah bahwa nilai indek CPUE hanya berdasarkan pada jumlah tangkapan ikan per-satuan upaya penangkapan tanpa mengikutsertakan variabel-variabel yang berpengaruh terhadapnya seperti strategi penangkapan, musim penangkapan, lokasi penangkapan dan kondisi lingkungan perairan [1], [4], [10], [19] [20], [24]. Sehingga penetapan indeks CPUE yang hanya berdasarkan pada jumlah ikan per upaya penangkapan tidak dapat menggambarkan kondisi aktual dari sumberdaya perikanan itu sendiri [4], [19], [20], [24]. Perlu dilakukan upaya standarisasi CPUE dengan mengikutsertakan variabelvariabel tersebut dalam analisis non parametrik dan fungsi linier.…”
Section: Pendahuluanunclassified
“…Nilai CPUE hasil tangkapan longline 2006-2015 mengalami kenaikan dan penurunan. Nilai rata-rata CPUE ALB 0.253 dengan kisaran antara 0.117-0.519 [8]. Nilai CPUE tertinggi terdapat pada tahun 2012.…”
Section: Hasil Dan Pembahasanunclassified
“…Tahun 2015 terdapat peraturan pelarangan kapal asing di Indonesia, sehingga CPUE ALB mengalami penurunan tajam. Faktor musim, jumlah pancing antar pelampung, dan daerah penangkapan mempengaruhi secara signifikan CPUE ALB [8]. Atas dasar inilah penelitian ini dibuat, untuk mengetahui seberapa besar interaksi faktor-faktor yang mempengaruhi hasil tangkapan ALB dengan mengetahui nilai signifikan masing-masing faktor, dengan penambahan faktor kombinasi umpan.…”
unclassified